The University Corporatization Shift: A Longitudinal Analysis of University Admission Handbooks, 1980 to 2010 - Davidson, Cliff (Canadian Journal of Higher Education, 2015)
This paper explores university corporatization and its impact on university literature, examining the frequency and placement of content in the admissions handbooks (viewbooks) of six Ontario universities from 1980 to 2010, at five-year intervals. Government budget cuts implemented in the mid-1990s served as a point of interest in the timing of corporatization. Content analysis showed a decreased emphasis on academics and an increased emphasis on the university experience; academics moved toward the back of the viewbooks, and student experience and university-specific advantages moved toward the front. The timing of these changes, however, did not correlate, as expected, with government budget cuts of the mid-1990s.